Medical Emergencies in Dental Practice - A Nepalese study - Joshi, Sandhya; Acharya, Sudeep (Orthodontic Journal of Nepal, 2015)
Introduction: Medical emergencies can occur in dental practice anytime. Changing demographics in the population and increased life expectancy have resulted in more people having medical conditions which predispose to a medical emergency. Objective: To find the prevalence of medical emergencies in dental practice in Nepal, to assess the preparedness of dentists to manage emergency situation, to find out the ways to improve their preparedness, and to determine the factors affecting the occurrence of medical emergency. Materials & Method: A cross-sectional study using self-administered questionnaire was done among one hundred and twenty four participants present at the 16th Annual Dental Conference. The questionnaire consisted of 15 questions. The data were analyzed using chi-square test and cross tabulation was performed to evaluate categorical variables at a significant level of p< 0.05. Result: The percentage of respondents who reported at least one emergency situation was 37.1%. Majority of the events occurred during oral surgical treatment. According to the survey, the most frequently encountered emergency condition was vasovagal syncope followed by hypoglycemia and seizures. The emergency events were managed by the respondents through various modalities. The dental graduates despite BLS training were found to feel incompetent to manage emergency events. Conclusion: Medical emergencies in dental practice in Nepal are frequent and not as rare as anticipated. Thus periodic training should be provided to improve necessary clinical skills.